Effect of Technology on Service Quality Perception and Patient Satisfaction- A study on Hospitals in Bangladesh - Emon, Md Mehedi Hasan; Khan, Tahsina; Alam, Monzurul (International Journal of Research and Applied Technology (INJURATECH), 2023)
This study investigates the intricate dynamics of technology's influence on service quality perception and patient satisfaction in Bangladesh's healthcare sector, a vital component of emerging economies. Focusing on the interplay between technology, service quality, and patient satisfaction, the research employs a quantitative approach, utilizing a structured questionnaire survey conducted both online and in-person among patients in private hospitals in Dhaka city. Statistical analyses, including correlation and regression, were applied to the gathered data. Key findings reveal significant correlations between service quality dimensions (responsiveness, assurance, communication, and discipline) and patient satisfaction. Notably, technology-related factors, specifically the use of tips, negatively impact satisfaction levels. Regression analysis identifies responsiveness, assurance, communication, and tips as significant predictors of patient satisfaction. Limitations, including the exclusive focus on Dhaka city's private hospitals, underscore the necessity for broader research across diverse healthcare settings to enhance generalizability. Practical implications recommend healthcare providers prioritize improving responsiveness, assurance, and communication, considering patient preferences on technology-related practices like tipping. From a societal perspective, the study emphasizes the broader importance of optimizing technology to elevate patient experiences, contributing to overall well-being. The research's originality lies in its nuanced examination of technology's influence on service quality and patient satisfaction within the distinctive context of Bangladeshi private hospitals. Acknowledging its limitations, this study encourages future research to explore technology's impact on service quality across various healthcare settings, providing valuable insights for ongoing improvements.